Strategic maturity desiderata of corporate capabilities - model ad its empirical veryfication - Nogalski, Bogdan; Niewiadomski, Przemysław (Management and Administration Journal, 2020)
The subject of the research of this elaboration are strategic maturity desiderata of the corporate capability of manufacturing enterprises operating in the agricultural machinery sector. The vital goal of this study is to determine the level of partial (functional) maturities constituting the strategic capability of the investigated enterprises. Achieving the main objective required the formulation and implementation of partial goals, which were applied to outline: nomination of desiderata determining strategic maturity (literature query), compilation of the research model in the form of an assessment sheet (literature exploration and expert research) and recognition of the level of strategic maturity among manufacturers of the agricultural machinery sector (theoretical model validation). The considerations contained in the paper are embedded in social sciences, and more specifically; in the field of management and quality sciences.